Tumor Necrosis Factor-Alpha (TNF-Alpha) And Intercellular Adhesion Molecule-1 (ICAM-1) Expression of Plasmodium Berghei Infected Swiss Mice Treated with Red Fruit (Pandanus Conoideus Lam) Ethanol Extract - Demianus Tafor; Achmad Djunaidi; Widya Wasityastuti; Eti Nurwening Sholikhah (Tropical Medicine Journal, 2013)
ABSTRACTIntroduction: Malaria infection could activate T cell helper 2 CD4+ which release cytokines IL-4, IL-5, IL-10 was a kind of immunosuppressant cytokines and prevented a cerebral tissue damage from the expression intercellular adhesion molecule-1 (ICAM-1) by TNF-α, ended with a cerebral malaria. The red fruit was proved as antioxidant but its effect to reduce TNF-α and expression of ICAM-1 in cerebral tissue endothelial cell remained unknown.Objectives: to know the effect of red fruit ethanol extract toward the change of TNF-α secretion number and ICAM-1 in Swiss male mice’s cerebral endothelial cell infected with P.berghei.Methods: Sixty Swiss male mice were divided in to 6 groups, group I was not given the red fruit (BM) ethanol extract and not infected P.berghei, Group II was given BM 260mg/kg BB but not infected P.berghei, group III, IV, V were given BM  130, 260, and 520 mg/kg respectively and infected with P.berghei. Red fruit extract or carrier substance was given for 4 weeks, P.berghei was given in the early of third week. TNF-α level check was done in third and ninth day after the injection, with TNF-α ELISA kit mouse. ICAM-1 cerebral endotel cell expression check was done in third and nine day with immunohistochemistry (IHC) coloring.Results: TNF-α level in third day after infected to the groups given red fruit extract (group III, IV, and V) showed no significant difference (p=0,839) compared to group which was not given red fruit but infected (group VI). TNF-α level in ninth day after infected to groups given red fruit ( group III,IV,V) lower (p<0,05) compared to groups which was not given red fruit but infected. ICAM-1 expression in third and ninth day after treatment to group given red fruit extract was lower (p<0,05) compared to groups given red fruit extract but infected. Conclusion: Red fruit ethanol extract ( P conoideus Lam) could decrease TNF-α level and ICAM-I expression in Swiss mice’ endothelial cerebral cells after infected by P.berghei.Key word: Pandanus conoideus Lam, TNF-α, ICAM-1 expression, Plasmodium berghei, Swiss mice